Solubilized antigen of Blastocystis hominis facilitates the growth of human colorectal cancer cells, HCT116 - Chandramathi, S.; Suresh, K.; Kuppusamy, U.R. (2010)
Blastocystis hominis is one of the most common intestinal protozoan parasites in humans, and reports have shown that blastocystosis is coupled with intestinal disorders. In the past, researchers have developed an in vitro model using B. hominis culture filtrates to investigate its ability in triggering inflammatory cytokine responses and transcription factors in human colonic epithelial cells. Studies have also correlated the inflammation by parasitic infection with cancer. The present study provides evidence of the parasite facilitating cancer cell growth through observing the cytopathic effect, cellular immunomodulation, and apoptotic responses of B. hominis, especially in malignancy. Here we investigated the effect of solubilized antigen from B. hominis on cell viability, using peripheral blood mononuclear cells (PBMCs) and human colorectal carcinoma cells (HCT116). The gene expressions of cytokines namely interleukin 6 (IL-6), IL-8, tumor necrosis factor alpha, interferon gamma, nuclear factor kappa light-chain enhancer of activated B cells (a gene transcription factor), and proapoptotic genes namely protein 53 and cathepsin B were also studied. Results exhibited favor the fact that antigen from B. hominis, at a certain concentration, could facilitate the growth of HCT116 while having the ability to downregulate immune cell responses (PBMCs). Therefore, there is a vital need to screen colorectal cancer patients for B. hominis infection as it possesses the ability to enhance the tumor growth.